A construção da identidade profissional do pedagogo - Rocha, Aline Sarmento Coura (2014)
This research approaches the construction of the pedagogue professional identity as the study objective, whose investigation issue is to find out what is the relevance of the Pedagogy course to construct the pedagogue professional identity and how do the legal curricular guidelines of the course contribute to form the future professional. We started from the hypothesis that the Pedagogy course is proposed in a general and fragmented manner in the National Curricular Guidelines; therefore, the result can be a professional without a defined identity and a fragile formation that can bring consequences to the professional s performance. With the aim of understanding how the pedagogue professional identity is built in the graduation process, the research proposed the following: carrying out a survey on the academic production of the pedagogue s formation process; identifying the controversies or contradictions that surround the discussion on such issue and the ideas of formation and professionalization of pedagogues in the syllable proposal of the course; and investigating on how does the Pedagogy course contribute to the professional identity construction. The methodology included documental and bibliographic research together with a case study and history of the thematic life of students from the last year of a Pedagogy course, from a private institution in the State of São Paulo, Brazil. The critical theory of Frankfurt s School was the main theoretical referential. In the debate about the results obtained after the research, we observed that students notice the emphasis in the formation in order to teach, but they still emphasize the lack of elements that may contribute to a better articulation between theory and praxis. The study also shows that there are contradictions to be defeated in the National Curricular Guidelines and in the elaboration of the Pedagogical Project of Pedagogy Course. Finally, there is still fragility with respect to the constitution of the pedagogue professional identity. It happens mainly because the institutions of higher education try to implement what has been stated in the National Curricular Guidelines, which are ruled in general competences and skills as identity axes of a professional profile that points out a fragility in the initial formation, providing consequences for their professional performance.